Latinitas curialis na przykładzie Epistulae gratulatoriae Benedykta XVI. Przybliżenia leksykalne i stylistyczne - Gacia, Tadeusz (Vox Patrum, 2022)
The study discusses selected aspects of the contemporary Latinitas ecclesiastica, especially its variation called Latinitas curialis, in nine congratulatory letters of Pope Benedict XVI. The author of the article analyzes the vocabulary related to the main topic of the letters - priestly and bishop ordination and their jubilees, as well as the occurrence of cursus, i.e. a system of rhythmic cadences consisting in the appropriate sequence of stressed and unstressed syllables. The terms for ordinations and their anniversaries come from very old source texts, only to a lesser extent this vocabulary is new; the formulas of papal blessings at the end of the letters retain the unchanged literary shape, traditional vocabulary and the same style. Cursus, present in the Latin papal curia, with slight breaks from the end of antiquity, appears in the analyzed letters in its four varieties: cursus planus, velox, tardus and trispondaicus.